Strategi Pembelajaran Pada Masa Covid-19 di Madrasah Aliyah 7 Bungkal Ponorogo Tahun Pelajaran 2020/2021 - Ahmad Dardiri; Nia Yunia Sari (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2022)
This research is motivated by the spread of the Covid-19 virus in various parts of the world. All sectors were affected. One of them is the education sector. Even though it is currently in the period of the Covid-19 epidemic, learning must continue. Various policies have been taken by the government to support the implementation of learning. Many schools are affected by the current situation. One of them is Madrasah Aliyah Muhammadiyah 7 Bungkal Ponorogo. In the learning process as a teacher, you must have a method or strategy so that the material can be conveyed to students so that the curriculum targets can be completed. This research to determine the impact caused by the presence of covid-19, learning process constraints and learning strategies used by teachers during the Covid-19 epidemic at Madrasah Aliyah Muhammadiyah 7 Bungkal Ponorogo. This research is a research with a qualitative approach. The design of this research is descriptive qualitative. Data collection techniques used in this study include observation, interviews and documentation. To analyze data using data reduction, data presentation and drawing conclusions. The results of this research indicate that the impact of Covid 19 is that learning becomes ineffective. MA Muhammadiyah 7 Bungkal currently uses online and offline learning strategies and collaborates both, or better known as